Body Shaming Dan Kepercayaan Diri: Studi Kasus Pada Remaja Putri - Gita Citra Tama; Abdinur Batubara (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Body shaming is an act of belittling someone based on their physical appearance, which has a negative impact on self-confidence, especially in adolescent girls. This study aims to examine the effect of body shaming on the self-confidence of adolescent girls in the social environment and media. The methods used are observation and literature study with a qualitative approach. Observations were made by observing the behavior of adolescents at school and their interactions on social media, while the literature study collected various literature on body shaming, self-confidence, and adolescent psychology. The results of the study showed that body shaming has a significant impact on decreasing the self-confidence of adolescent girls, which can affect their mental and social well-being. Adolescents who often experience body shaming tend to feel inferior, avoid social interactions, and have the potential to experience psychological disorders such as depression. This study is expected to provide insight to the public, especially educators and parents, regarding the importance of stopping the practice of body shaming and supporting the formation of healthy self-confidence in adolescent girls.